2015
DOI: 10.1002/bjs.10040
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide-enhanced MRI at 3 T for accurate axillary staging in breast cancer

Abstract: SPIO-enhanced MRI at 3 T is useful for accurate diagnosis of metastatic sentinel nodes, indicating that sentinel node biopsy may be avoided in patients with breast cancer who have non-metastatic sentinel nodes on imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…A number of radiological techniques have been tried in the past to increase the sensitivity of recognition of metastatic axillary lymph nodes before treatment. Evans and colleagues showed that mean stiffness at shear wave elastography in combination with grey‐scale ultrasonography is an independent predictor of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of radiological techniques have been tried in the past to increase the sensitivity of recognition of metastatic axillary lymph nodes before treatment. Evans and colleagues showed that mean stiffness at shear wave elastography in combination with grey‐scale ultrasonography is an independent predictor of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the lymphatic system notoriously difficult to locate during a dissection without additional contrast. Several contrast agents have been employed to assist in sentinel node biopsy in patients and the most well‐known contrast agents that are used for surgical and medical imaging purposes in patients are, Evans blue, patent blue (Tsopelas and Sutton ), indocyanine green (Yamamoto et al ; Guo et al ), 99m Tc nanocolloid for lymphoscintigraphy (Schicha ; Ballardini et al ) and superparamagnetic iron oxide particles for MRI (Pouw et al ; Rubio et al ; Motomura et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Early and sensitive cancer diagnosis along with effective treatment are critical for favorable outcomes. Superparamagnetic iron oxide (SPIO) nanoparticles have been successfully used for staging and treatment monitoring of a variety of cancers with magnetic resonance imaging (MRI) [2,3]. Since imagers have successfully delivered SPIO to cancers through intravenous injection [4-6], we can build on decades of this experience and use these same probes as Trojan horses for the delivery of therapeutic drugs to cancers.…”
Section: Introductionmentioning
confidence: 99%